1996
DOI: 10.1111/j.1570-7458.1996.tb00791.x
|View full text |Cite
|
Sign up to set email alerts
|

The importance of non‐pollen plant parts as food sources for the common blossom thrips, Frankliniella schultzei

Abstract: Like other flower thrips, Frankliniella schultzei Trybom (Thysanoptera: Thripidae) feeds on pollen. However, the influence of a pollen diet on the life history of F. schultzei may not be as significant as reported for other thrips species. Frankliniella schultzei was reared successfully and with low mortalities (≤20%) on Wax Mallow, (Malvaviscus arboreus Cav.) plant part diets. Development times and fecundity on a petal diet were not significantly different from that on a pollen diet. Fecundity on a diet combi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
37
0

Year Published

2000
2000
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(37 citation statements)
references
References 17 publications
0
37
0
Order By: Relevance
“…It is well-known that its massive occurrence takes place during the flowering of the plants which are most attractive for the insect (Khosbayar 2001), but it is not sure whether this phenomenon is due to obviously better accessibility to high quality pollen, because of more arthropods or because of both. Some entomologists ascribe no important role to pollen as far as the development of the thrips is concerned (Milne et al 1996;Nakao 1999), while others are convinced that it plays an important part in this game (Tsai et al 1996).…”
Section: Resultsmentioning
confidence: 97%
“…It is well-known that its massive occurrence takes place during the flowering of the plants which are most attractive for the insect (Khosbayar 2001), but it is not sure whether this phenomenon is due to obviously better accessibility to high quality pollen, because of more arthropods or because of both. Some entomologists ascribe no important role to pollen as far as the development of the thrips is concerned (Milne et al 1996;Nakao 1999), while others are convinced that it plays an important part in this game (Tsai et al 1996).…”
Section: Resultsmentioning
confidence: 97%
“…Adult males were excluded from the analysis because the most direct effects of the host on F. schultzei populations are probably through dietary effects on larval development and female fecundity. Female adults were identified using the methods of Milne et al . (1996b).…”
Section: Methodsmentioning
confidence: 99%
“…Teulon & Penman, 1991). However, Milne et al . (1996) concluded that a diet containing pollen was no more beneficial to Frankliniella schultzei (Trybom) thrips larvae than a diet containing other floral parts, suggesting no adaptive benefits from the inclusion of pollen in the diet.…”
Section: Introductionmentioning
confidence: 99%